Using pictures to improve vocabulary learning in the english language with students of 6th and 7th years of basic education at “José Rafael Arízaga Vega” school. Academic year 2013-2014 - Quezada Quezada, Gina Micaela (2015)
The purpose of this action research study was focused on the use of pictures in the improvement of vocabulary learning with 13 sixth and seventh year students at “José Rafael Arízaga Vega” school. A twelve-session intervention plan was carried out to improve the vocabulary learning. A researcher-made test was used to measure the students‟ advancement in the 5 parameters that vocabulary learning process implies. Observation guides were also utilized to confirm the students‟ learning growth. The results of the posttest revealed important progress in vocabulary learning using pictures. Based on these results, it might be concluded that the evolution in the students‟ learning concerning vocabulary was significant. A recommendation for future teachers is to include the use of pictures frequently in their classes and to follow the logical process of teaching to consolidate learning.